Interações no ensino-aprendizagem de literatura em EaD: análise semiótica de discursos e práticas - Moraes, Carlos Wiennery da Rocha (2021)
This thesis investigates how the interaction in literature classes of a discipline of a degree in languages/literature occurs and/or is simulated. This discipline is offered by distance learning (DE) by a public university in the state of Tocantins, the State University of Tocantins – UNITINS. For this, we consider two resources used by this teaching modality for the formation of teachers: video classes and forums. The general objective of this thesis was to analyse analyze how the interactions mediated by tutors in literature forums take place, as well as mobilizing strategies in these forums and in video classes, considering the way they competed in two directions: the formation of the literary reader and the formation of the future literature teachers. As a theoretical foundation, we mobilize studies of education, literary literacy and discursive semiotics, mainly from the social semiotic aspect, since it prioritizes the meaning produced in the interaction between subjects and between subjects and objects, with implications for a reflection on interaction regimes in teaching. In this sense, the corpus analyzes prioritized the dimension of the enunciation modes and interaction regimes. The research is of a qualitative and interpretative nature, with documentary analysis and case study. As a corpus, there are video classes, forums and interviews with graduates and tutors. The analyzed forums comprise discussions promoted by the discipline of Portuguese Literature II between the months of May and June 2015, offered on the Educ@ UNITINS / UAB platform. The interviews were carried out from 2019 to 2020. We considered as the corpus of the research: i) video classes (in total of seven with more than two hours of recorded didactic material); ii) interactions of alumni and tutors at a distance, in seven discussion forums (totaling more than six hundred interventions) and, iii) semi-structured interview with eleven interlocutors (six graduates and five distance tutors). From the analysis carried out, we defend the centrality of the interactional processes in teaching-learning that emerges as one of the biggest challenges that are imposed for distance learning. Despite the resources, this interaction is still fragile in terms of the quality of exchanges between professor, tutors and academics, as they ocurred mainly in the sense that semiotics defines as a programming regime, resulting in repetition and little or no effective production of meaning. From the point of view of the formation of readers, the historicizing and sociological perspective that little attention is given to the literary text does not seem to favor the effective conjunction of readers with literature. As a result, repeating a traditional training already condemned by researchers in the field, and even by official documents, such as National Curriculum Parameters (BRAZIL, 1998; 1999) and Common Curricular National Base (BRAZIL, 2018; 2019), the literature classes in question privilege knowledge about the literary to the detriment of reading itself, which does not contribute to subjects – even in function of their social class, with little experience as reading subjects – to effectively form themselves as teachers capable of arousing the taste and interest in the literary.